2013
DOI: 10.1002/ajim.22179
|View full text |Cite
|
Sign up to set email alerts
|

Who Pays for Work‐Related Traumatic Injuries? Payer Distribution in Washington State by Ethnicity, Injury Severity, and Year (1998–2008)

Abstract: This study demonstrated the importance of considering differential access to other insurance coverage and adaptation by health care settings to financial pressures when assessing trends in occupational injury incidence and reporting, especially when using WC as a proxy for work-relatedness. The addition of occupation, industry, and work status to trauma registries and hospital discharge databases would improve surveillance, research, policy and prevention efforts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
47
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(50 citation statements)
references
References 59 publications
1
47
1
1
Order By: Relevance
“…There may be a contributory survival shift effect (ie, targeted fatality prevention efforts preventing death but not severe injury or severe injury less often proving fatal due to trauma system improvements). These potential collective or alternative mechanisms have been discussed at more length in previous related publications 21 37 38…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…There may be a contributory survival shift effect (ie, targeted fatality prevention efforts preventing death but not severe injury or severe injury less often proving fatal due to trauma system improvements). These potential collective or alternative mechanisms have been discussed at more length in previous related publications 21 37 38…”
Section: Discussionmentioning
confidence: 96%
“…They may also include changes in the covered workforce, increases in contingent or precarious employment and/or decreasing identification or reporting of minor injuries as being work related 4 5. Adaptation to financial pressures by healthcare providers, as well as changes in access to health insurance coverage other than WC, may have an especially important impact on observed occupational injury trends when using WC as a proxy for work-relatedness 12 38…”
Section: Discussionmentioning
confidence: 99%
“…It also negatively affects her understanding of her pain, her communication with health care providers and educators, and her overall prognosis. (Medical Report) 11 RTW with the Accident Employer…”
Section: Health Carementioning
confidence: 99%
“…Studies have similarly identified language disparities in access to workers' compensation, which provides victims of occupational injuries or illnesses with benefits and services such as income replacement, health care and vocational services. Evidence from Canada and the United States indicates that injured linguistic minorities are more likely than their counterparts to file a workers' compensation claim, perhaps because they have more severe injuries, or they more often lack alternative sources of income replacement [10][11][12]. However, research suggests that those who file a claim have inferior experiences and outcomes [10,[13][14][15][16][17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…More flexible work arrangements, including multiple jobholding which has been linked to a higher incidence of fatalities (Bush, McKee, & Bunn, 2013), can also complicate resolution of claims even where coverage is established. Evidence indicates that there is significant under-reporting and the failure to lodge or succeed with workers' compensation claims even in the case of death or serious injuries at work (Sears, Bowman, Adams, & Silverstein, 2013). For example, in 2008-09 the families of 276 (or 26%) of the 400 workers fatally injured at work received workers' compensation while the families of 124 (or 31%) did not (Safe Work Australia, 2012c).…”
Section: Introductionmentioning
confidence: 99%